Micro-Raman investigations on zirconium oxide film during swift heavy ion irradiation to study crystalline-to-crystalline phase transformation kinetics by cascade overlap model - Singh, Fouran; Rawat, Mukesh; Gautam, Subodh K.; Ojha, Sunil (Journal of Applied Physics, 2019)
In situ micro-Raman studies are reported to monitor the evolution of the tetragonal phase in a monoclinic zirconium oxide thin film under swift heavy ion irradiation with increasing ion fluences. Structural changes in the irradiated film are observed as compared to the virgin sample, evident from an evolution of the tetragonal phase beyond critical ion fluence. The interpretation of experimental data allows for an in-depth understanding of irradiation induced stiffening of phonon and crystalline-to-crystalline phase transformation in ZrO2 thin films. Irradiation induced peak broadening and uniform shifting of fundamental Raman modes are observed mainly in the anion (i. e., oxygen atom) dominant frequency region and give a direct indication of the accumulation of structural disorder in the oxygen sublattice of the ZrO2 film. A qualitative approach is followed to understand the kinetics of such a crystalline-to-crystalline phase transformation. Experimental results reveal that the cascade overlap model with the requirement of about six multiple ion impacts provides an excellent fit to data, and the same is further confirmed by x-ray diffraction data. Thus, this study suggests that such in situ studies envisage a better and more authentic insight into the kinetics of phase transformations under similar nonequilibrium conditions.